Aspergirls : empowering famales with asperger syndrom - Simone, Rudy; Willey, Liane Holliday (London : Jessica Kingsley, 2010)
Girls with Asperger's Syndrome are less frequently diagnosed than boys, & even once symptoms have been recognized, help is often not readily available. The image of coping well presented by AS females can often mask difficulties, deficits, challenges, & loneliness
Includes biliographical references (p. 235-236)
Keywords: Asperger's Syndrome; Women with mental disabilities -- Life skills guides; Women with mental disabilities -- Anecdotes